Historique du rapatriement - Rémillard, Gil (Les Cahiers de droit, 1984)
April 17, 1982, will be one of the most important dates in the history of Canadian federalism. On that date, the Canada Bill, voted several days before by the Parliament of Westminster became the Constitution Act, 1982: the Canadian Constitution had been patriated. This article gives the history of this patriation from the beginning of the talks on this subject after the first World War of 1914-18 to the unfinished constitutional compromise of 1982.